2020
DOI: 10.1016/j.jpubeco.2020.104241
|View full text |Cite
|
Sign up to set email alerts
|

Sheltering in place and domestic violence: Evidence from calls for service during COVID-19

Abstract: The COVID-19 pandemic has led to an economic slowdown as more people practice social distancing and shelter at home. The increase in family isolation, unemployment, and economic stress has the potential to increase domestic violence. We document the pandemic's impact on police calls for service for domestic violence. The pandemic increased domestic violence calls by 7.5% during March through May of 2020, with effects concentrated during the first five weeks after social distancing began. The increase in report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
315
4
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(349 citation statements)
references
References 26 publications
20
315
4
10
Order By: Relevance
“…Following the lead of previous reviews, also in our work we found a sharp spike in DV cases reported around the globe (Agüero 2020; Baig et al 2020;Barbara et al 2020;Boserup et al 2020;Bradley et al 2020;Chandan et al 2020;Gebrewahd et al 2020;Ghoshal et al 2020;Goh et al 2020;Gosangi et al 2020;Jarnecke et al 2020;Jetelina et al 2020;Kaukinen et al 2020;Kofman et al 2020;Kumar 2020;Leslie et al 2020;Mahase et al 2020;Mazza et al 2020;Neil 2020;Nigam 2020;Piquero et al 2020;Qin et al 2020;Roesch et al 2020;Roseboom et al 2020;Sifat 2020;Telles et al 2020;Tochie et al 2020;Vieira et al 2020;Yahya et al 2020;Zargham et al 2020). For example, Aguero (2020) in a study conducted in Peru, one of the several countries which imposed a national lockdown in March, found that the incidence rate of calls to helplines centres increased around 48% between April and July 2020.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Following the lead of previous reviews, also in our work we found a sharp spike in DV cases reported around the globe (Agüero 2020; Baig et al 2020;Barbara et al 2020;Boserup et al 2020;Bradley et al 2020;Chandan et al 2020;Gebrewahd et al 2020;Ghoshal et al 2020;Goh et al 2020;Gosangi et al 2020;Jarnecke et al 2020;Jetelina et al 2020;Kaukinen et al 2020;Kofman et al 2020;Kumar 2020;Leslie et al 2020;Mahase et al 2020;Mazza et al 2020;Neil 2020;Nigam 2020;Piquero et al 2020;Qin et al 2020;Roesch et al 2020;Roseboom et al 2020;Sifat 2020;Telles et al 2020;Tochie et al 2020;Vieira et al 2020;Yahya et al 2020;Zargham et al 2020). For example, Aguero (2020) in a study conducted in Peru, one of the several countries which imposed a national lockdown in March, found that the incidence rate of calls to helplines centres increased around 48% between April and July 2020.…”
Section: Resultssupporting
confidence: 81%
“…According to Graham-Harrison (2020), in Cyprus, when the first quarantine was putting in reality, were asked to people to stay indoors, and afterwards calls to the violence helpline numbers shot up by over 30%. Also, in the U.S., the study conducted by Leslie et al (2020) showed how the COVID-19 pandemic was associated with a 7.5% increase in domestic violence service calls during the 12 weeks after the start of lockdown. Effects were even most considerable in the first five weeks when calls for DV increased by around 10% (Leslie et al 2020).…”
Section: The Coursementioning
confidence: 99%
“…As schools closed, this important source of reports also disappeared. See Leslie and Wilson (2020) for evidence that DV likely increased. For rape there may be an undercount for similar reasons, but possibly not to the same extent.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent papers focus specifically on the impact of the pandemic onset on domestic violence. Examining calls for service from 14 municipalities, Leslie and Wilson (2020) find an increase of 7.5% in the first several weeks after the onset of the pandemic, although they are not able to distinguish real crime changes from changes in reporting patterns. Another paper focuses just on domestic violence incident reports in Dallas and finds weak evidence for an increase ( Piquero et al, 2020 ).…”
Section: Introductionmentioning
confidence: 83%
“…1 To date, the focus of the debate over safer-at-home orders has been on their efficacy of transmission suppression and the implicit trade-off between lives saved and reduced economic activity. Safer-at-home orders have resulted in serious negative impacts on Americans in several dimensions: studies have shown large impacts on the labor market, mental health, and domestic violence incidents, for instance (e.g., Adams-Prassl et al (2020) ; Beland et al (2020) ; Brodeur et al (2021) ; Leslie and Wilson (2020) ).…”
mentioning
confidence: 99%